La Contaminación del Río Zamora y su influencia en la salud de los habitantes de Sauces Norte. - Calva Arrobo, Nancy Jalene (2013)
In the city of Loja, although collectors are marginal, at the height of Northern Willows neighborhood wastewater is poured directly into the river Zamora, this health problem as the people living in this sector especially those who have their homes nearby. For this reason the research was conducted: "RIO ZAMORA POLLUTION AND ITS INFLUENCE ON THE HEALTH OF THE POPULATION OF SAUCES NORTE" to determine the level of biological contamination of the Rio Zamora in this sector, the possible forms of pollution and identifying most frequent diseases. The research proposed sampling the Zamora River water collected at three sites as: Zamora Huayco, Mercado Mayorista and Sauces Norte, determining their quality through laboratory physical, chemical and bacteriological, for which we used the protocol SVAP (Visual Assessment Stream Protocol) described by Mafla (2005). We also carried out a survey of 706 Sauces Norte local people and direct observation of the researcher to evaluate forms of pollution, finally reviewed the epidemiological profile and the results of stool tests conducted at the School of the neighborhood called "Pompilio Reinoso" allowing identify the most common diseases in this population. The most significant results are related to the concentration of total and fecal coliforms in this sector, which is 3.2E +03 NMP/100ml, in terms of biochemical oxygen demand is also high, with 120 mg / l. Another important aspect is the perception and observation of the population by 60.91% reported having observed that the river water is used for agriculture. The epidemiological profile shows that if there is a parasitoids (7.86%) and EDA (4.26), more than a high degree of parasitoids in school children is 88%. Finally we can say indirectly that the inhabitants of Norte Sauces if exposed to contamination through consumption of crops that are irrigated with this water.